Optimalisasi Kualitas Citra Radiograf Menggunakandan Digital Radiography (DR) Pada Pemeriksaan Anatomi Thorax Proyeksi Antero - Posterior(AP) - Angella, Shelly; Hulmansyah, Danil; Annisa, Aulia (Innovative: Journal Of Social Science Research, 2025)
Thorax radiographic examination is one of the most commonly used diagnostic methods in the medical world. With the advancement of technology, the use of Digital Radiography (DR) has become standard in many healthcare facilities. This study aims to evaluate and optimize the technical parameters in thorax radiography imaging to obtain the best image quality that allows for a more accurate and efficient diagnosis. This study involved the collection of AP thorax radiograph image data from various patients using DR devices. Variations in technical parameters such as exposure factors were analyzed to determine their effect on image quality. Image quality is evaluated based on criteria such as SNR. The evaluation was carried out through the dicom viewer application. The analysis is carried out to determine the combination of technical parameters that produce the best image quality. The trial was done by changing one parameter at a time while keeping other parameters constant to see how they affected image quality. It is expected that the optimal combination of exposure factors will result in maximum image quality, improve diagnostic capabilities, and reduce radiation exposure in patients. This study is expected to provide recommendations for the use of optimized parameters in clinical practice for AP thorax examination, as well as additional training for radiographic technicians so that the application of these parameters can be carried out consistently. The results of this study show that the optimal combination of exposure factors can produce maximum image quality, improve diagnostic capabilities, and reduce radiation exposure in patients. The output of this study is a recommendation for the use of parameters that have been optimized in clinical practice for AP thorax examination published in a nationally accredited journal.